Prediction of tendency to addiction based on alexithymia and assertiveness in nursing students - Kazemi-Rezaei SV (Fiyz̤, 2020)
Background: Given the high prevalence of addiction, it is essential efforts to identify the risk factors for this problem in different populations. Therefore, the present study aimed to predict the tendency of addiction based on the amount of alexithymia and assertiveness in nursing students. Materials and Methods: The research design was correlational. The sample consisted of 160 nursing students of Kermanshah University of Medical Sciences and Kermanshah Azad University who were studying in the academic year of 2018-19 and were selected by cluster sampling. Data were collected using Weed and Butcher addiction potential scale, Toronto alexithymia scale, and Gambrill and Richey assertiveness questionnaire. Pearson correlation and multivariate regression analysis were used to analyze the data. Data were analyzed by SPSS-24 software. Results: The results of Pearson correlation coefficient showed that there is a positive significant relationship between alexithymia and with nursing students' tendency to addiction and there is a negative significant relationship between assertiveness and their tendency to Addiction (P<0.01). The results of multivariate regression analysis also revealed that 23% of the variance in active addiction preparation is explained by alexithymia and assertiveness (R2= 0.230). Also, 67.7% of the variance of passive addiction preparation is explained by alexithymia and assertiveness (R2= 0/67/7). Conclusion: According to the results of the study, it seems that two components of alexithymia and assertiveness with addiction preparation are related to addiction and cause nursing students to tend to addiction and need the attention of the educational system to reduce emotional arousal and improve assertiveness through holding workshops.